2020
DOI: 10.1021/acs.chemrestox.0c00304
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Models to Predict the Perturbation of Molecular Initiating Events Related to Thyroid Hormone Homeostasis

Abstract: Disturbance of the thyroid hormone homeostasis has been associated with adverse health effects such as goiters and impaired mental development in humans and thyroid tumors in rats. In vitro and in silico methods for predicting the effects of small molecules on thyroid hormone homeostasis are currently being explored as alternatives to animal experiments, but are still in an early stage of development. The aim of this work was the development of a battery of in silico models for a set of targets involved in mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Several thyroid disease detection and classification approaches have been presented in the literature. For example, Garcia et al [ 9 ] predicted the high probable molecules initiating the thyroid hormone homeostasis using machine learning algorithms RF, LR, GBM, SVM, and deep neural networks (DNN). The early prediction of the molecules is helpful for further testing in the first stages of thyroid disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several thyroid disease detection and classification approaches have been presented in the literature. For example, Garcia et al [ 9 ] predicted the high probable molecules initiating the thyroid hormone homeostasis using machine learning algorithms RF, LR, GBM, SVM, and deep neural networks (DNN). The early prediction of the molecules is helpful for further testing in the first stages of thyroid disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study reported an external BA equal to 0.85 that is analogous to the accuracy values observed on the TeS for the BRF and KNN models presented here, but the performance of the PLR model is associated a much lower prediction coverage (i.e., 54.5% for the PLR model). Recently Garcia de Lomana et al (2020) , proposed a set of models predicting the interference of small molecules with nine targets involved in the thyroid hormone homeostasis (deiodinase 1, 2 and 3, transtiretrin, TPO, thyroid releasing hormone receptor and thyroid stimulating hormone receptor). Models were developed using five machine learning algorithms in combination with three data balancing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…(Quantitative) structure–activity relationship models [(Q)­SARs] are in silico models allowing screening of large chemical inventories based on quantitative data (QSAR) or qualitative data (SAR) where the potency of chemicals to induce an MIE are related to their structural and physico-chemical properties. Attempts have earlier been made to develop first-tier predictive tools to identify chemicals of concern for their potency to modulate the endocrine system, either focusing on one or several compound classes or targeting a limited number of protein targets related to different hormone systems. Recently, a battery of QSAR models for some of the thyroid-specific MIEs was developed with several classical machine learning methods …”
Section: Introductionmentioning
confidence: 99%
“…21−23 Recently, a battery of QSAR models for some of the thyroid-specific MIEs was developed with several classical machine learning methods. 24 In the current study, our first aim was to develop first-tier predictive QSAR models able to identify potential THDCs with confidence using the Conformal Prediction (CP) framework with the underlying Random Forest. Models were built for all MIEs related to the TH system as recently described by Noyes et al, 11 where data for model development is available.…”
Section: ■ Introductionmentioning
confidence: 99%